GrpEL1 overexpression mitigates hippocampal neuron damage via mitochondrial unfolded protein response after experimental status epilepticus - Minjia Xie; Xin Wu; Xi Liu; Longyuan Li; Feng Gu; Xinyu Tao; Bingyi Song; Lei Bai; Di Li; Haitao Shen; Zongqi Wang; Wei Gao (Neurobiology of Disease, 2025)
Background: Despite the availability of various antiepileptic treatments, approximately 30 % of epilepsy patients remain refractory to conventional therapies, underscoring the need for neuroprotective strategies. This study investigates the role of GrpEL1 in modulating the mitochondrial unfolded protein response (UPRmt) and its potential protective effects on hippocampal neurons following experimental status epilepticus (SE). Methods: The effects of GrpEL1 were assessed in vivo using a Lithium-pilocarpine rat model of SE and in vitro with glutamate-treated HT22 hippocampal cells. Protein expression and interactions were analyzed by Western blot, immunofluorescence, and co-immunoprecipitation. Neuronal survival was evaluated through Nissl staining. Mitochondrial function was evaluated aggresome formation, mitochondrial membrane potential (MMP) assays, mitochondrial oxygen consumption rate (OCR) measurements, and behavioral assessments using the Morris water maze. Results: In the SE rat model, mtHSP70 levels were significantly upregulated in mitochondria, while GrpEL1 expression remained relatively stable. Overexpression of GrpEL1 led to a reduction in neuronal damage and improved functional recovery post-SE. In vitro, GrpEL1 overexpression enhanced the GrpEL1-mtHSP70 interaction, reduced the accumulation of misfolded proteins, and decreased neuronal apoptosis. Furthermore, GrpEL1 overexpression mitigated mitochondrial dysfunction by preserving MMP and improving mitochondrial bioenergetics, as evidenced by enhanced mitochondrial OCR. Conclusion: GrpEL1 plays a crucial role in maintaining mitochondrial proteostasis and mitigating hippocampal neuronal injury following SE by regulating UPRmt. These findings suggest that GrpEL1 may represent a promising target for therapeutic intervention to protect against seizure-induced neurodegeneration.